THE EFFECT OF VISUAL APPEAL , ASKING PRICE , USER EXPERIENCE , AND BRAND ADVOCACY ON USER SATISFACTION OF MYIM3 MOBILE APPLICATION (STUDY ON STUDENTS OF MALIKUSSALEH UNIVERSITY) - Farah Anissa; Adnan; Naufal Bachri; Khairina AR (Journal of Accounting Research, Utility Finance and Digital Assets, 2025)
This study examined the influence of visual appeal, asking price, user experience, and brand advocacy on user satisfaction among students at Malikussaleh University in Lhokseumawe who use the MyIM3 mobile application. The respondents were 110 students selected using non-probability and purposive sampling techniques based on specific criteria: age, amount of pocket money, gender, faculty, use of the Indosat mobile operator, and active use of the MyIM3 application. A Google Form was used to gather data, and SPSS version 22 was used for analysis. The results indicate that visual appeal, user experience, and brand advocacy positively and significantly affected user satisfaction. These findings suggest that an attractive interface, ease of use, and peer recommendations are key factors in enhancing student satisfaction with the application. In contrast, asking price does not significantly affect user satisfaction. Based on these findings, it is recommended that Indosat prioritize improving the visual design of the application, ensuring a clean user interface and a stable system to minimize technical issues such as bugs and errors. Although pricing was not a significant factor in this study, offering attractive price promotions may still be beneficial. Continuous evaluation and development of the application are essential to maintain and enhance user satisfaction. This study highlights the importance of application quality and user-centered design in promoting satisfaction among student users.